Effects of ilaprazole on the steady-state pharmacodynamics of clopidogrel in healthy volunteers: An open-label randomized crossover study - Ye, Zekang; Chen, Pengsheng; Tan, Chuchu; Gong, Xiaoxuan; Li, Ran; Dong, Zhou; Ullah, Inam; Zhou, Chen; Zhou, Sufeng; Xie, Lijun; Hou, Xuemei; Han, Zhihui; et al. (Frontiers in Pharmacology, 2022)
Background: Previous studies have suggested that proton pump inhibitors could impair the antiplatelet effect of clopidogrel. It is uncertain whether ilaprazole affects the antiplatelet effect of clopidogrel. This study aimed to determine the drug-drug interaction between ilaprazole and clopidogrel. Methods: A randomized crossover trial of 40 healthy subjects was performed. Clopidogrel was administered alone or in combination with ilaprazole for 7 days. The maximal platelet aggregation (MPA) to 5 μmol/L adenosine diphosphate was measured by light transmission aggregometry and the platelet reactivity index (PRI) was determined by vasodilator-stimulated phosphoprotein P2Y12 assay. High on-treatment platelet reactivity (HOPR) was defined as a MPA of >40%. The inhibition of platelet aggregation (IPA) and PRI in the two phases were compared between two regimens after the last dosing. Results: IPA was comparable between the two regimens at 0h, 10h and 24h (P>0.05), but higher at 4h in the clopidogrel alone regimen compared with that in the combined treatment regimen (75.66 ± 18.44% vs. 70.18 ± 17.67%, P=0.031). The inhibition of PRI was comparable between the two regimens at 0h and 24h. There were no significant differences in the area under the time-IPA% curve (AUC) or the incidence of HOPR at all time-points between the two regimens. Conclusions: In healthy subjects, ilaprazole has limited effect on the pharmacodynamics of clopidogrel and it may not be clinically relevant. Trial registration: Trial registration number: www.chictr.org.cn ChiCTR2000031482. Registered 02 April 2020.